2017
DOI: 10.1159/000452356
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Plays a Key Role in Non-Steroidal Anti-Inflammatory Drug-Induced Small Intestinal Damage

Abstract: Background: Non-steroidal anti-inflammatory drugs (NSAIDs) damage the small intestine by causing multiple erosions and ulcers. However, to date, no established therapies and prophylactic agents are available to treat such damages. We reviewed the role of intestinal microbiota in NSAID-induced intestinal damage and identified potential therapeutic candidates. Summary: The composition of the intestinal microbiota is an important factor in the pathophysiology of NSAID-induced small intestinal damage. Once mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 37 publications
0
54
0
14
Order By: Relevance
“…Accumulating evidences suggest that intestinal bacteria may play a significant role in the pathogenesis of small-bowel dam-age induced by NSAIDs and that enterobacterial translocation into the mucosa represents the first step of a series of events leading to gross lesion formation. 66,67 It has been reported that germ-free mice were resistant to NSAIDs related intestinal damage. 68,69 However, when germ-free mice were colonized with jejunal bacteria from PPI-treated rats, the severity of NSAIDinduced intestinal injury increased.…”
Section: Intestinal Microbiota Modulationmentioning
confidence: 99%
“…Accumulating evidences suggest that intestinal bacteria may play a significant role in the pathogenesis of small-bowel dam-age induced by NSAIDs and that enterobacterial translocation into the mucosa represents the first step of a series of events leading to gross lesion formation. 66,67 It has been reported that germ-free mice were resistant to NSAIDs related intestinal damage. 68,69 However, when germ-free mice were colonized with jejunal bacteria from PPI-treated rats, the severity of NSAIDinduced intestinal injury increased.…”
Section: Intestinal Microbiota Modulationmentioning
confidence: 99%
“…Proton pump inhibitor may induce dysbiosis of intestinal microbiota and exacerbate the small intestinal damage such as erosions/ulcers. We consider that intestinal microbiota plays a crucial role in NSAID-induced small intestinal damage [9]. Novel therapy modulating the composition of the intestinal microbiota could be developed for such small intestinal damages [10].…”
Section: Utility Of Ce In Ogibmentioning
confidence: 99%
“…Although most of the interactions between a host and its commensal microbiota and their metabolites are symbiotic, changes in the composition and function of the gut microbiota, called “dysbiosis”, are thought to be associated with various kinds of diseases [1,2]. Intestinal dysbiosis has been demonstrated to be associated with inflammatory bowel disease (IBD) [3,4], irritable bowel syndrome [5], and nonsteroidal anti-inflammatory drugs-induced enteropathy [6]. Moreover, gut dysbiosis has been reported in patients with types 1 and 2 diabetes [7,8], multiple sclerosis [9], autism [10], and rheumatoid arthritis [11].…”
Section: Introductionmentioning
confidence: 99%